Modular Assembly of a Concatenated DNA Circuit for In Vivo Amplified Aptasensing. Issue 21 (23rd April 2022) - Wu, Qiong; Yang, Lei; Xie, Lingling; Shang, Jinhua; He, Shizhen; Liu, Jing; Wang, Fuan
Abstract: Probing endogenous molecular profiles in living entities is of fundamental significance to decipher biological functions and exploit novel theranostics. Despite programmable nucleic acid‐based aptasensing systems across the breadth of molecular imaging, an aptasensing system enabling in vivo imaging with high sensitivity, accuracy, and adaptability is highly required yet is still in its infancy. Artificial catalytic DNA circuits that can modularly integrate to generate multiple outputs from a single input in an isothermal autonomous manner, have supplemented powerful toolkits for intracellular biosensing research. Herein, a multilayer nonenzymatic catalytic DNA circuits‐based aptasensing system is devised for in situ imaging of a bioactive molecule in living mice by assembling branched DNA copolymers with high‐molecular‐weight and high‐signal‐gain based on avalanche‐mimicking hybridization chain reactions (HCRs). The HCRs aptasensing circuit performs as a general and powerful sensing platform for precise analysis of a series of bioactive molecules due to its inherent rich recognition repertoire and hierarchical reaction accelerations. With tumor‐targeting capsule encapsulation, the HCRs aptasensing circuit is specifically delivered into tumor cells and allowed the high‐contrast imaging of intracellular adenosine triphosphate in living mice, highlighting its potential for visualizing these clinically important biomolecules and for studying the associated physiological processes. Abstract : A multilayer concatenated catalytic aptasensing scheme is developed for in vivo aptasensing via the in situ self‐assembly of branched DNA copolymers with low mobility and numerous fluorophores. With an auxiliary tumor‐specific nanocarrier, the versatile HCRs aptasensing circuit enables the in vivo aptasensing of tumor cells with high sensitivity, high accuracy, and high adaptability.